Kaedah menjayakan pelaksanaan dinar emas sebagai instrumen wakaf / Che Khadijah Hamid and Surita Hartini Mat Hassan - Hamid, Che Khadijah; Mat Hassan, Surita Hartini (Universiti Teknologi MARA, Sabah, 2020)
Gold Dinars has gained a great interest from the public in 1998 – 2002 and it continued a few years after. The hype slowly fades as the time passes by. This research study is seen as the right medium for the researchers to spark the interest again; searching for new approaches towards its planning, strategies, and also implementation. The main focus is mainly on the cash waqf practice in which this paper aims to ratify the accountability of gold dinars as one of the medium for waqf practice. So, the researchers have outlined two objectives; to identify reliable methods for gold dinars as waqf practice and to formulate sustainability of gold dinars as waqf practice. This research study adopts qualitative methods whereas the data collection will be collected based on interviews from selected experts in waqf practice. Then, data collected were analyzed using content analysis. As a result, this paper proposes four methods; First, Urgency and Influential Methods on Government. Secondly, Collaboration of R & D Research Group and The Parliament. Thirdly, Waqf Practice Objectives and Options. Fourthly, Collaboration of Professional and Religious Fields. Stabilizing Funds Methods and Recommendation has also been identified as one of the approaches which should be practiced by Waqf Institution. Significantly, these proposed approaches serve as a unique idea for the Waqf institution to preserve the perpetuity of the Waqf property and also the practice.